Metal organic framework material with hollow structure and preparation method thereof, solid-phase micro-extractant containing metal organic framework material and preparation method and application of solid-phase micro-extractant

By developing the metal organic frame material H-ZIF-8@Zn-MOF-74 with a hollow structure, the problem of lack of mesoporosis in the material in the prior art is solved, and pesticide residues are effectively adsorbed, which improves pesticide wastewater treatment. Efficiency and adsorption volume demonstrate high sensitivity and environmental protection.

CN119192599AInactive Publication Date: 2024-12-27LANZHOU FOOD & DRUG INSPECTION & TESTING INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411336038.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of mesoporosis and free space inside the existing metal-organic frame materials limits the penetration and diffusion of analytes, making it difficult to effectively adsorb pesticide residues, affecting the efficiency of pesticide wastewater treatment.

Method used

Developed a metal organic frame material H-ZIF-8@Zn-MOF-74 with a hollow structure, pre-synthesized ZIF-8 by 2-methylimidazole and Zn(NO3)2, and 2,5-dihydroxy terephthalene diphenyl Formic acid is converted as a ligand to form a sea urchin-shaped hollow structure, providing more reaction sites and specific surface area, and enhancing adsorption performance.

Benefits of technology

It has achieved efficient adsorption of nitrogen-containing pesticides, improved the removal efficiency and adsorption amount of pesticide wastewater treatment, and demonstrated the characteristics of high sensitivity, simple operation and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192599A_ABST
    Figure CN119192599A_ABST
Patent Text Reader

Abstract

The invention provides a metal organic framework material with a hollow structure and a preparation method thereof, a solid-phase micro-extraction agent containing the metal organic framework material, and a preparation method and application of the solid-phase micro-extraction agent. The metal organic framework material is formed by synthesizing ZIF-8 from 2-methylimidazole and Zn (NO3) 2.6 H2O, and then performing ligand conversion and etching on the ZIF-8 through 2, 5-dihydroxy terephthalic acid. The metal organic framework material is of a hollow shell structure, the shell structure comprises a hollow shell layer and a plurality of rod-shaped structures located outside the hollow shell layer, the metal organic framework material keeps the main form of a ZIF-8 dodecahedron, the protruding rod-shaped structures continuously extend outwards, and richer reaction sites and larger specific surface area are provided. The invention further provides a solid-phase microextractant containing the metal organic framework material and application of the solid-phase microextractant, and the method has the outstanding advantages of being high in sensitivity, easy to operate, environmentally friendly and the like, has high removal efficiency and large adsorption capacity on nitrogen-containing pesticides (ONPs) and can be applied to rapid detection of environmental samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal organic framework materials and wastewater treatment, and specifically relates to a metal organic framework material with a hollow structure and a preparation method, a solid phase microextraction agent containing the metal organic framework material and a preparation method and application. Background Art

[0002] The widespread use of pesticides is a key factor in ensuring the output and quality of agricultural products, and provides anchoring support for the development of modern agriculture. Different types of pesticides with different functions (such as organophosphorus, organic nitrogen, organochlorine and carbamate) have been widely used to minimize agricultural productivity losses caused by pests, pathogens and weeds. However, non-standard use may lead to excessive pesticide residues, endangering the quality of agricultural products, which not only restricts the development of my country's agricultural product export trade, but also seriously affects the health of consumers. Abused pesticides can also enter the water environment through the ecosystem and have been detected in soil, water sources, etc. Therefore, it is very important to strengthen the monitoring and removal of pesticide residues.

[0003] During the pretreatment process, a large amount of interfering substances are extracted during the extraction of pesticide residues, which not only increases the difficulty of sample preparation, but also causes potential accumulation hazards to the detection instruments. So far, the most commonly used methods are high performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). At the same time, some other methods, including capillary electrophoresis and pressurized capillary electrochromatography, have also been reported sporadically. In recent years, the rapid, green and efficient new sample pretreatment technologies developed are often used for sample purification, separation, concentration and concentrated extraction, mainly including dispersed liquid-liquid microextraction (DLLME), liquid-liquid extraction (LLE), solid phase extraction (SPE), magnetic solid phase extraction (MSPE), solid phase microextraction (SPME), etc. Since its introduction by Borissin and colleagues in 1990, SPME has attracted widespread attention as a powerful green sample pretreatment technology due to its outstanding advantages of high sensitivity, simple operation and environmental protection. In order to obtain the target substances in complex sample matrices without being affected by interfering impurities, it is necessary to further explore the excellent materials of SPME coatings. Therefore, in the past few years, researchers have been continuously looking for the development and preparation of new materials, such as carbon nanomaterials, molecularly imprinted polymers, metal organic frameworks (MOFs), covalent organic frameworks (COFs), ionic liquids, etc.

[0004] Currently, based on MOFs and MOF-derived materials, the penetration and diffusion of analytes are limited due to the lack of mesopores and free space inside the solid materials. Therefore, this application aims to develop hollow MOFs as adsorbents for extracting analytes. Summary of the invention

[0005] In order to solve the above-mentioned problems in the prior art, the present invention provides a metal organic framework material with a hollow structure and a preparation method, a solid phase microextraction agent containing the metal organic framework material and a preparation method and application. Among them, the metal organic framework material is named H-ZIF-8@Zn-MOF-74, and the metal organic framework material contains 2-methylimidazole, 2,5-dihydroxyterephthalic acid and Zn(NO3)2. A single metal organic framework material is a shell structure, and the shell structure includes a hollow shell layer and a plurality of rod-like structures located outside the hollow shell layer. Specifically, the metal organic framework material maintains the main morphology of the ZIF-8 dodecahedron, and the protruding rod-like (also called rod-like) structure continues to extend outward, providing more abundant reaction sites and a larger specific surface area. The metal organic framework material is coated on a stainless steel wire and applied to the treatment of pesticide wastewater. Due to its unique hollow structure and larger specific surface area, it provides more active sites for adsorption and exhibits excellent adsorption performance.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a metal organic framework material with a hollow structure, the metal organic framework material is named H-ZIF-8@Zn-MOF-74, the metal organic framework material is pre-synthesized ZIF-8 by 2-methylimidazole and Zn(NO3)2, and then ligand conversion is performed by 2,5-dihydroxyterephthalic acid, and etching is formed; a single metal organic framework material is a shell structure, and the shell structure includes a hollow shell layer and a plurality of rod-like structures uniformly located outside the hollow shell layer. Among them, 2-methylimidazole Zn(NO3)2 is made into ZIF-8, and 2,5-dihydroxyterephthalic acid is used as a ligand to exchange with part of 2-methylimidazole to form a hollow metal organic framework material. The formation of the hollow structure is caused by the difference in zinc density between ZIF-8 and Zn-MOF-74.

[0008] In some feasible embodiments, the shell structure is in the shape of a sea urchin; the specific surface area of ​​the metal organic framework material is 500 to 1000 m 2 g -1 ; The diameter of a single metal organic framework material is 150 to 250 nm.

[0009] The second aspect of the present invention provides a method for preparing a metal organic framework material, specifically the preparation of H-ZIF-8@Zn-MOF-74, which is to first synthesize the metal organic framework ZIF-8, use 2,5-dihydroxyterephthalic acid (H4DOBDC) as a ligand conversion agent, and ZIF-8 as a functional material, and obtain a sea urchin-shaped hollow H-ZIF-8@Zn-MOF-74 metal organic framework material through the solvent thermal conversion strategy of the present invention.

[0010] Specifically, the synthesis principle diagram of the metal organic framework material (H-ZIF-8@Zn-MOF-74) of the present application is shown in Figure 1 .like Figure 1 As shown, the pre-synthesized ZIF-8 nanoparticles and 2,5-dihydroxyterephthalic acid (H4DOBDC) were ultrasonically dissolved in N,N-dimethylformamide (DMF), and the mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene lined tube, reacted at 110°C for 12 hours, and then placed at room temperature, repeatedly washed with dimethylformamide (DMF) and methanol, centrifuged, and dried to obtain the product. After that, it was physically bonded to the stainless steel wire etched by aqua regia with silicone sealant, and it can be used for selective adsorption of ONPs.

[0011] In some specific examples, the preparation method of the metal organic framework material comprises the following steps: 1) dissolving Zn(NO3)2·6H2O and 2-methylimidazole in an alcohol solvent, and reacting at 50-80°C for 10-30 minutes; drying the obtained product at 50-70°C to obtain ZIF-8, i.e., an organic metal framework material having a ZIF-8 framework structure, wherein a single framework of the material presents a ZIF-8 framework structure;

[0012] Preferably, the temperature is crucial to the formation of the metal organic framework structure, and the temperature can be selected from 50 to 55°C, 55 to 65°C, 65 to 75°C, 75 to 80°C. Preferably, the temperature is 65 to 75°C.

[0013] Optionally, the reaction time can be 10 to 15 min, 15 to 20 min or 20 to 30 min, preferably 15 to 20 min.

[0014] Optionally, in step 1), the amount of alcohol solvent added is selected as required.

[0015] Preferably, in step 1), 2-methylimidazole is first dissolved in an alcohol solvent to obtain solution A; then Zn(NO3)2·6H2O is dissolved in an alcohol solvent to obtain solution B; then solution A is added to solution B to react. Solution A and solution B need to be fully stirred respectively. In addition, the method of adding solution A and solution B is very important. The best structure and morphology of the metal organic framework can be obtained by adding solution A to solution B. More preferably, solution A is quickly added to solution B. Rapidly can be understood as 1s to 30s, which can of course be adjusted according to the amount of solvent.

[0016] More preferably, in solution A, the mass of the alcohol solvent is 5 to 10 times the mass of 2-methylimidazole, and can be 5, 6, 7, 8, 9 or 10 times. In solution B, the mass of the alcohol solvent is 15 to 20 times the mass of Zn(NO3)2·6H2O, and can be 15, 16, 17, 18, 19 or 20 times.

[0017] Preferably, in step 1), the post-treatment is to wash the product with an alcohol solvent and ultrapure water for 1 to 5 times, preferably 3 times respectively.

[0018] Preferably, in step 1), the alcohol solvent is selected from C1-C4 alcohols, such as methanol or ethanol.

[0019] Preferably, in step 1), the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 2 to 2.5:1, preferably 2.3 to 2.4:1. 2) 2,5-dihydroxyterephthalic acid and ZIF-8 are dissolved in DMF respectively, and mixed to obtain a mixture;

[0020] The mixture is sealed in a reactor and reacted at 100-120° C. for 9-15 hours. The product obtained by post-treatment is dried at 50-70° C. to obtain H-ZIF-8@Zn-MOF-74, which is a metal organic framework material with a hollow structure.

[0021] Preferably, the reaction temperature is crucial to the formation of the framework structure of H-ZIF-8@Zn-MOF-74. The temperature is generally 100-120°C. The multiple rod-like structures of the formed metal-organic framework located outside the hollow shell are more compact, and the metal-organic framework of H-ZIF-8@Zn-MOF-74 has a large specific surface area. The preferred temperature is 105-110°C.

[0022] Preferably, the mass ratio of 2,5-dihydroxyterephthalic acid to ZIF-8 is 1:2.5-2.8. It can be 1:2.5-2.6, 1:2.6-2.7 or 1:2.7-2.8. In a preferred embodiment, the ratio is 11.89:30.

[0023] Preferably, in step 2), the mixture is reacted in a stainless steel autoclave, and a fully enclosed reaction is directly carried out.

[0024] Preferably, in step 2), the post-treatment is to wash the product with DMF and methanol solvents for 1 to 5 times each, preferably 3 times each.

[0025] The third aspect of the present invention is a metal organic framework material prepared by the preparation method of the second aspect.

[0026] The fourth aspect of the present invention provides a solid phase microextraction agent, which includes a solid phase carrier and a coating coated on the solid phase carrier, and the coating is the metal organic framework material as described in the first aspect, or the metal organic framework material as described in the third aspect; the solid phase carrier is stainless steel wire.

[0027] Preferably, the coating and the solid carrier are connected by physical adhesion, and the present application preferably uses silicone sealant for bonding.

[0028] Preferably, the thickness of the coating is 5 to 30 nm, and the coating can be performed according to actual needs, generally 5 to 10 nm, 10 to 15 nm, 15 to 20 nm, 20 to 25 nm or 25 to 30 nm.

[0029] And / or, the stainless steel wire is aqua regia modified stainless steel wire.

[0030] In a fifth aspect, the present invention provides a method for preparing the solid phase microextraction agent according to the fourth aspect, comprising the following steps:

[0031] 1) immersing the stainless steel wire in an adhesive that is completely dispersed by ultrasonic wave, and using the adhesive to attach the metal organic framework material to the stainless steel wire to obtain a uniform coating; repeating the operation to obtain a solid phase microextraction agent with a target coating thickness;

[0032] Preferably, the stainless steel wire is aqua regia modified stainless steel wire, and the modification method is to first soak the stainless steel wire (SSW) in aqua regia solution for 1 to 5 minutes, then wash it with methanol and water for 1 to 5 times respectively, and dry it at room temperature.

[0033] Optionally, the target coating thickness is 5 to 30 nm, specifically 5 to 10 nm, 10 to 15 nm, 15 to 20 nm, 20 to 25 nm or 25 to 30 nm.

[0034] Preferably, the adhesive is a mixed solution of silicone sealant and toluene, and the concentration of silicone sealant in the adhesive is 450-550 mg / mL -1 , you can choose according to your actual needs.

[0035] 2) Dry the coated solid phase microextractor at 110-130°C for 1-5 hours to obtain a solid phase microextractor. Generally, it is dried at 120°C for 3 hours. In a specific example, the stainless steel wire (SSW) is first etched rough in aqua regia solution, and then the etched SSW is alternately immersed in a mixture of silicone sealant / toluene solution and H-ZIF-8@Zn-MOF-74, and the process is repeated multiple times to ensure the uniformity of the material. Finally, the homemade stainless steel wire fiber (solid phase microextractor) is dried at 120°C for 3 hours and stored at room temperature before use.

[0036] The present invention has the following technical effects including but not limited to:

[0037] 1) The metal organic framework in the metal organic framework material with a hollow structure of the present invention is a hollow shell structure, and there are multiple rod-like structures evenly distributed on the outside of the shell structure, that is, the metal organic framework material of the present application maintains the main form of ZIF-8 dodecahedron, and the protruding rod-like structure continues to extend outward, providing more abundant reaction sites and a larger specific surface area.

[0038] 2) The preparation method of the metal organic framework material of the present invention is simple, and the prepared metal organic framework material has a uniform and epitaxially grown core-shell structure, a large specific surface area, and a rich mesoporous structure, thus having the characteristics of strong adsorption capacity.

[0039] 3) The solid phase microextraction agent made of the metal organic framework material of the present invention has the outstanding advantages of high sensitivity, simple operation, and environmental friendliness, and has a high removal efficiency and a large adsorption capacity for nitrogen-containing pesticides (ONPs). BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the synthesis route and detection of sea urchin-shaped hollow metal-organic framework (H-ZIF-8@Zn-MOF-74) material.

[0041] Figure 2 This is a scanning electron microscope image of the rhombic dodecahedron ZIF-8.

[0042] Figure 3 This is a scanning electron microscope image of the sea urchin-shaped hollow metal-organic framework material (H-ZIF-8@Zn-MOF-74).

[0043] Figure 4 This is a transmission electron microscope image of the rhombic dodecahedron ZIF-8.

[0044] Figure 5 This is a transmission electron microscope image of the sea urchin-shaped hollow metal-organic framework material (H-ZIF-8@Zn-MOF-74).

[0045] Figure 6 This is a scanning electron microscope image of the stainless steel wire modified with aqua regia in Example 2;

[0046] Figure 7 This is a scanning electron microscope image of the stainless steel wire after the adhesion coating in Example 2;

[0047] Figure 8 Infrared spectra of ZIF-8, Zn-MOF-74, and H-ZIF-8@Zn-MOF-74.

[0048] Fig. 9 XRD patterns of ZIF-8, Zn-MOF-74, and H-ZIF-8@Zn-MOF-74.

[0049] Fig.10 N2 adsorption-desorption curve and pore size distribution diagram of H-ZIF-8@Zn-MOF-74.

[0050] Fig.11 TG and DTG graphs of H-ZIF-8@Zn-MOF-74.

[0051] Fig.12 This is the OAD orthogonal distribution diagram of H-ZIF-8@Zn-MOF-74.

[0052] Fig.13 The adsorption capacity of H-ZIF-8@Zn-MOF-74 for 6 pesticides (n=3).

[0053] Fig.14 This is the Langmuir isotherm adsorption model of six pesticides.

[0054] Fig.15 Freundlich isotherm adsorption model for six pesticides.

[0055] Fig.16 The adsorption kinetics of six pesticides on H-ZIF-8@Zn-MOF-74.

[0056] Fig.17 Pseudo-first-order kinetic model of H-ZIF-8@Zn-MOF-74 for six pesticides.

[0057] Fig.18 This is the pseudo-second-order kinetic model of H-ZIF-8@Zn-MOF-74 for six pesticides.

[0058] Fig.19 Extraction efficiency after 76 and 106 cycles for H-ZIF-8@Zn-MOF-74 fibers.

[0059] Fig. 20The extraction performance of six pesticides was compared between H-ZIF-8@Zn-MOF-74 fiber and two commercial SPME fibers (PDMS fiber and PA fiber).

[0060] Fig.21 Comparison of chromatograms of six ONPs solutions after extraction using H-ZIF-8@Zn-MOF-74 fiber. DETAILED DESCRIPTION

[0061] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0062] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0063] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0064] 1) The preparation method of Zn-MOF-74 used in the examples of the present application is:

[0065] A mixture of 1 g of 2,5-dihydroxyterephthalic acid (H4DOBDC) and 4.52 g of Zn(NO3)2·6H2O was dissolved in 100 mL of DMF. Then 5 mL of water was added and the tightly covered solution was placed in an oven at 110 °C for 24 h. The resulting solid was centrifuged and, after cooling to room temperature, washed three times with DMF and then twice with methanol. The solid product was soaked in methanol for 6 days. During this period, fresh methanol solvent was added three times after pouring out the old solvent. Finally, the methanol was removed under vacuum conditions at 150 °C for 1 h to obtain Zn-MOF-74 nanocrystals.

[0066] 2) The preparation method of the adhesive used in the examples of the present application is:

[0067] Silicone sealant was purchased from Anhui Shenzhou Spacecraft Rubber Industry Co., Ltd. (Banta Industrial Zone, Lai'an County, Chuzhou City, Anhui Province). 1.0 g of silicone sealant was dissolved in toluene to make 2.0 mL to prepare a mixed solution of silicone sealant and toluene as an adhesive. The concentration of silicone sealant in the adhesive was 500 mg mL -1 .

[0068] 3) The stainless steel wire used in the examples of the present application was purchased from Shanghai Gaoge Industry and Trade Co., Ltd.

[0069] 4) The commercial SPME fibers used in the comparative examples of the present application, namely polydimethylsiloxane (PDMS, 100 μm) and polyacrylate (PA, 85 μm) fibers were purchased from Supelco (Bellefonte, PA, USA), and are represented by PDMS fiber and PA fiber, respectively.

[0070] 5) The two environmental water samples used in the application example of this application are water samples from the lower reaches of Dongdagou and the lower reaches of Shiyang River; the three tea water samples are rose tea, black tea and green tea.

[0071] The metal organic framework material of the present invention is Fig. 9 It can be seen from the XRD diagram that the material has the characteristic diffraction peaks of ZIF-8 and Zn-MOF-74, so it is named ZIF-8@Zn-MOF-74, and because the material is hollow inside (Hollow), the final material is named H-ZIF-8@Zn-MOF-74. The metal organic framework with a hollow structure mentioned in the specification of this application is H-ZIF-8@Zn-MOF-74, which is also a sea urchin-shaped hollow metal organic framework material. The specification of this application mentions that ZIF-8 contains a ZIF-8 framework structure, and Zn-MOF-74 contains a Zn-MOF-74 framework structure. As a person skilled in the art, it can be understood that there will be no doubt.

[0072] Example 1

[0073] (1) Dissolve 2.9 g Zn(NO3)2·6H2O and 6.9 g 2-methylimidazole in 60 mL methanol (i.e., dissolve 2.9 g Zn(NO3)2·6H2O in 60 mL methanol and 6.9 g 2-methylimidazole in 60 mL methanol). Then, quickly pour the 2-methylimidazole alcohol solution into the Zn(NO3)2·6H2O alcohol solution, mix the two solutions thoroughly, and stir in a 70°C water bath for 15 minutes. Finally, wash the product three times with methanol and ultrapure water respectively, and then dry the product in an oven at 60°C to obtain a white product ZIF-8, which is an organic metal framework material with a ZIF-8 framework structure.

[0074] (2) 11.89 mg of 2,5-dihydroxyterephthalic acid (H4DOBDC) and 30 mg of ZIF-8 were dissolved in 50 mL of dimethylformamide (DMF). The mixture was transferred to a stainless steel reactor and reacted at 110 °C for 12 hours. The product was washed three times with dimethylformamide (DMF) and methanol, and then placed in an oven at 60 °C for drying to obtain a light yellow product H-ZIF-8@Zn-MOF-74, which is a metal organic framework material with a hollow structure.

[0075] Structural Verification

[0076] Figure 2 This is a scanning electron microscope image of ZIF-8. Figure 2 It can be seen that the individual particles of ZIF-8 present a regular rhombic dodecahedron structure, and the particles are evenly dispersed with an average particle size of 200 nm.

[0077] Figure 3 This is a scanning electron microscope image of the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74). Figure 3 As shown, the average particle size of a single metal organic framework is 200 nm. By using 2,5-dihydroxyterephthalic acid as a ligand to exchange part of the 2-methylimidazole ligands in ZIF-8, the main framework structure of the rhombic dodecahedron of ZIF-8 is maintained, and ZIF-8 is used as the basic core with dense rod-like protrusions extending outward.

[0078] Figure 4 This is a transmission electron microscope image of ZIF-8. Figure 4 It can be seen that the single particles of ZIF-8 show a solid rhombic dodecahedron structure, the particles are evenly dispersed, and the average particle size is 200 nm.

[0079] Figure 5 This is a transmission electron microscope image of a sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74). Figure 5 It can be seen that the average particle size of a single metal organic framework in the metal organic framework material is 200nm. 2,5-dihydroxyterephthalic acid is used as a ligand to exchange part of the 2-methylimidazole ligand in ZIF-8. H-ZIF-8@Zn-MOF-74 is based on ZIF-8, and gradually bulges outward. The dense rod-like protrusions extend outward, and the interior is hollow, forming a metal organic framework material with a hollow structure. The single particle of the metal organic framework material with a hollow structure presents a sea urchin-shaped hollow structure, which is called a sea urchin-shaped hollow metal organic framework structure. This structural transformation greatly increases the specific surface area of ​​the material and provides more favorable conditions for π-π stacking. After mechanism analysis, this sea urchin-shaped hollow metal organic framework structure is due to Zn2+ The ions escape outward. H-ZIF-8@Zn-MOF-74 composed of this sea urchin-shaped hollow metal organic framework exposes more abundant active sites. It is well known in the art that the adsorption capacity of metal organic framework materials for pesticides and other substances depends on the specific surface area of ​​the material and the exposed active stability. Therefore, when it is applied to the field of water treatment, it can induce the capture of a large amount of pesticides by relying on its large specific surface area and exposed abundant active sites, thereby improving the adsorption capacity and rate of the material.

[0080] Figure 8 FT-IR spectra of ZIF-8, Zn-MOF-74 and sea urchin-shaped hollow metal organic framework (H-ZIF-8@Zn-MOF-74). The C=O stretching vibration peak on the carboxyl group of the ligand appears at 1653 cm -1 With the formation of MOF (metal organic framework), the carboxyl group is gradually consumed, and the vibration peak at this time is significantly weakened. -1 and 3600cm -1 A broad peak appears between 1400 cm -1 To 1600cm -1 The peaks in the range represent the symmetric and asymmetric stretching vibrations of the carbon-oxygen bond (COC) in the ligand. -1 The characteristic peak at proves the existence of Zn-O bond. The above characterization confirms the successful synthesis of H-ZIF-8@Zn-MOF-74.

[0081] Fig. 9 The XRD spectra of ZIF-8, Zn-MOF-74 and sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) are shown in Figure 3. The XRD spectrum of ZIF-8 has obvious diffraction peaks at 7.25°, 10.50°, 12.65°, 14.73°, 16.45°, 18.10° and 26.81°, representing the crystal planes of (011), (002), (112), (022), (013), (222) and (134), respectively. In addition, Zn-MOF-74 has clear diffraction peaks at 6.65°, 11.60°, 17.94° and 31.42°, representing the crystal planes of (110), (300), (410) and (100), respectively. The sea urchin-shaped hollow metal-organic framework material (H-ZIF-8@Zn-MOF-74) has the characteristic diffraction peaks of ZIF-8 and Zn-MOF-74, indicating the successful preparation of H-ZIF-8@Zn-MOF-74.

[0082] Fig.10The N2 adsorption-desorption isotherms of the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) are shown in Figure 2. Fig.10 As shown in the figure, the N2 adsorption-desorption isotherm of the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) prepared in Example 1 belongs to the IV type isotherm and has an H3 type hysteresis loop, indicating that H-ZIF-8@Zn-MOF-74 is a mesoporous material with uniform pore size, which is consistent with the pore size distribution in the illustration. The specific surface area of ​​H-ZIF-8@Zn-MOF-74 is relatively high, reaching 838.01m 2 g -1 , aperture is 0.663cm 3 g -1 The average pore size is 3.167 nm. The ligand conversion strategy improves the original pore structure of ZIF-8, resulting in an increase in the proportion of mesoporous molecules in the composite material, which is beneficial to the mass transfer of pesticides.

[0083] The thermal stability of H-ZIF-8@Zn-MOF-74 was evaluated by thermogravimetric analysis (TGA). Fig.11 It can be seen that in the first stage of 25-200 ° C, due to the evaporation of water and solvent attached to the surface of H-ZIF-8@Zn-MOF-74, H-ZIF-8@Zn-MOF-74 lost 14% of its mass. The second stage is between 200-566 ° C, due to the loss of bound water in H-ZIF-8@Zn-MOF-74 and the separation of ligands, H-ZIF-8@Zn-MOF-74 lost 20% of its mass. Due to decarbonization, the third weight loss step occurred, and the mass loss of H-ZIF-8@Zn-MOF-74 was 39%. The results show that the H-ZIF-8@Zn-MOF-74 has good thermal stability and can meet the requirements of SPME (solid phase microextraction).

[0084] Effect verification

[0085] 1) To investigate the adsorption performance of sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) on ONPs, the following experiment was conducted. Adsorption capacity refers to the maximum adsorption amount per unit adsorbent at a certain temperature and adsorbent concentration. ONPs are 6 common nitrogen-containing pesticides: Chlorothalonil, Tebuconazole, Chlorpyrifos, Butralin, Deltamethrin, and Pyridaben.

[0086] Adsorption amount Q e Calculate using the following formula (1):

[0087]

[0088] Where V is the volume of the adsorbate solution, L; C0- is the original concentration of the six pesticides in the standard solution, mg L -1 ; C e - is the concentration of the supernatant after adsorption, mg L -1 ; m – is the mass of H-ZIF-8@Zn-MOF-74, g.

[0089] The adsorption capacity of sea urchin-shaped hollow metal-organic framework materials for ONPs was studied from two aspects: adsorption kinetics and adsorption thermodynamics. Fig.13 This is the adsorption kinetics experiment of 6 ONPs on the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74). With the increase of C0, the adsorption capacity of the adsorbent increased significantly, which is due to the unsaturated adsorption capacity. When C0 continued to rise to 40 mg L -1 When , the adsorption amount gradually reaches equilibrium, and the isotherm equation is fitted as shown in Fig.14 is the Langmuir isotherm adsorption model of six pesticides. Fig.15 It is the Freundlich isotherm adsorption model of six pesticides. Using the Langmuir isotherm and Freundlich isotherm to fit the adsorption thermodynamic data, it can be seen that the adsorption capacity of the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) is more consistent with the Langmuir isotherm adsorption model (R L 2 >R F 2 ), the adsorption process is mainly monolayer adsorption. The Langmuir and Friedrich isotherm models are close to 1, indicating that the active sites on the surface of the sea urchin-shaped hollow metal-organic framework material (H-ZIF-8@Zn-MOF-74) are occupied by the adsorbent and tend to be saturated. This is related to the hollow epitaxial growth structure of the sea urchin-shaped hollow metal-organic framework material. Fig.13 It can be seen that the maximum adsorption capacity of the sea urchin-shaped hollow metal organic framework material (H-ZIF-8@Zn-MOF-74) for six common nitrogen-containing pesticides, Chlorothalonil, Tebuconazole, Chlorpyrifos, Butralin, Deltamethrin, and Pyridaben, are 31.82, 19.67, 26.96, 52.59, 18.67, and 25.46 mg g, respectively. -1 .

[0090] 2) The adsorption performance of H-ZIF-8@Zn-MOF-74 for pesticides in Example 1 was studied experimentally.

[0091] Adsorption amount Q e Calculate using the following formula (1):

[0092]

[0093] Where V is the volume of the adsorbate solution, L; C0- is the original concentration of the six pesticides in the standard solution, mg L -1 ; C e - is the concentration of the supernatant after adsorption, mg L -1 ; m – is the mass of H-ZIF-8@Zn-MOF-74, g.

[0094] like Fig.16 The dynamic adsorption performance of H-ZIF-8@Zn-MOF-74 was further studied by the adsorption kinetic model. It can be found that the pseudo-first-order kinetic model ( Fig.17 ) is significantly lower than the pseudo-second-order kinetic model ( Fig.18 ), H-ZIF-8@Zn-MOF-74 is more consistent with the pseudo-second-order kinetic model (R2 2 >R1 2 ), indicating that H-ZIF-8@Zn-MOF-74 mainly undergoes chemical adsorption, accompanied by physical adsorption such as pore adsorption and electrostatic adsorption.

[0095] 3) The stability and repeatability of H-ZIF-8@Zn-MOF-74 in Example 1 were studied experimentally, and a cycle test was performed. Fig.19 As shown, after repeated use for 76 and 106 times, the extraction loss rates of 6 pesticides by solid phase microextraction of H-ZIF-8@Zn-MOF-74 were 9.1% and 14.2%, respectively. At the same time, H-ZIF-8@Zn-MOF-74 was weighed and visually inspected. There was no significant change in the weight of H-ZIF-8@Zn-MOF-74 before and after adsorption, and the material had good adhesion without shedding. The results show that the prepared H-ZIF-8@Zn-MOF-74 has good stability and reproducibility.

[0096] Example 2

[0097] Preparation of solid phase microextraction agent, physical adhesion method The H-ZIF-8@Zn-MOF-74 material prepared in Example 1 was bonded to the surface of modified stainless steel wire (SSW). First, the SSW was immersed in aqua regia solution for 3 min, then washed three times with methanol and water respectively, and dried at room temperature. Secondly, it was immersed in an adhesive that was completely dispersed by ultrasound, and the powder of the H-ZIF-8@Zn-MOF-74 material was attached to the SSW with the adhesive to obtain a uniform coating. The operation was repeated three times to obtain the desired SPME coating thickness, such as Figure 6 Before coating, Figure 7 After coating, the coating thickness was (337.4-298.6) nm / 2 = 19.4 nm. Finally, the homemade fiber was dried at 120 °C for 3 hours to obtain a solid phase microextraction agent, named H-ZIF-8@Zn-MOF-74 fiber, and stored at room temperature before use.

[0098] Figure 6 This is a scanning electron microscope image of the stainless steel wire modified by aqua regia. Figure 6 It can be seen that the surface of the stainless steel wire is etched, and a uniform rough outer layer appears.

[0099] Figure 7 This is a scanning electron microscope image of the stainless steel wire after the coating is adhered in Example 2. Figure 7 It can be seen that the surface of the stainless steel wire is evenly adhered with metal-organic framework materials, making it rougher.

[0100] Application Example 1

[0101] The H-ZIF-8@Zn-MOF-74 fiber prepared in Example 2 is placed in the water sample to be treated, and the extraction time (Et) is controlled to be 10 to 50 minutes, and can be any value within the range; the desorption time (Dt) is controlled to be 2 to 10 minutes, and can be any value within the range; the extraction temperature (ET) is 25 to 45°C, and can be any value within the range; the stirring speed (St) is 300 to 500 rpm, and can be any value within the range; the salt concentration (NaCl) is 0 to 12%, and can be any value within the range.

[0102] Then, the OAD L25 (55) experimental method was used to comprehensively evaluate the comprehensive effects of various experimental conditions on the experimental results to obtain the optimal extraction efficiency of H-ZIF-8@Zn-MOF-74 fiber material for 6 ONPs. ONPs are 6 common nitrogen-containing pesticides: Chlorothalonil, Tebuconazole, Chlorpyrifos, Butralin, Deltamethrin, and Pyridaben. The experimental conditions and test results within the range are shown in Table 1. In Table 1, Et represents the extraction time, ET represents the extraction temperature, and Fig.12 As shown in Table 1, the orthogonal experimental results show that the 13th orthogonal array experiment obtained the best experimental conditions, namely, extraction time of 30 minutes, desorption time of 6 minutes, extraction temperature of 30°C, stirring speed of 500 rpm, and NaCl salt concentration of 9% (w / v). Subsequent experiments will be carried out under this condition.

[0103] Table 1

[0104]

[0105]

[0106]

[0107] 3) Validation of analytical methods

[0108] Under the optimal conditions selected in Application Example 1, the performance of the solid phase microextraction method of H-ZIF-8@Zn-MOF-74 fiber in Example 2 was evaluated. The experimental conditions data and test results are shown in Table 2. The results show that the method has a good linear range (0.072-1000 μg L -1 ), correlation coefficient (R 2 ) was greater than 0.9915, and the minimum detection limit (LOD) and quantification limit (LOQ) were between 0.021 and 0.422 μg L -1 and 0.072-1.406 μg L -1 The relative standard deviation (RSD) was 0.26%-5.27%, and the intra-day and inter-day accuracies were 0.24%-4.18% and 0.39%-4.28%, respectively. The experimental results show that this method has the characteristics of high sensitivity and good practicality.

[0109] Table 2

[0110]

[0111]

[0112] 4) Finally, the extraction performance of H-ZIF-8@Zn-MOF-74 fiber in Example 2 was investigated.

[0113] Bare silicone sealant wire: that is, in Example 2, the powder adhesion of the H-ZIF-8@Zn-MOF-74 material is not performed, and the modified stainless steel wire (SSW) is only put into the ultrasonically dispersed adhesive, and then dried to obtain the bare silicone sealant wire.

[0114] ZIF-8 fiber: The H-ZIF-8@Zn-MOF-74 material in Example 2 is replaced by ZIF-8, and the other aspects are the same, to obtain ZIF-8 fiber.

[0115] like Fig.21 As shown, the H-ZIF-8@Zn-MOF-74 fiber of Example 2 has excellent adsorption performance and better extraction ability, and the preparation material is simple, environmentally friendly, accurate and reliable.

[0116] Comparative Example

[0117] Comparison with Commercial SPME Fibers

[0118] In order to evaluate the ONPs enrichment ability of H-ZIF-8@Zn-MOF-74 fiber in Example 2, we compared it with commercially available fibers (PDMS fiber and PA fiber). Fig. 20 As shown, compared with PDMS fibers and PA fibers, the H-ZIF-8@Zn-MOF-74 fibers of Example 2 exhibited excellent adsorption performance, which was due to their unique hollow structure and larger specific surface area, providing more active sites for adsorption.

[0119] Application Example 2

[0120] Under the selected optimal conditions, two environmental water samples and three tea water samples were tested to verify its practicality. Except for pyridaben, the other five ONPs were detected in the real samples. The concentrations ranged from 0.4932 to 8.353 μg L -1 The pesticide concentrations in both water samples were lower than those in GB5749-2022.

[0121] To verify the accuracy of the method, the standard addition method was used, and two concentrations were added to determine the recovery rate. The experimental conditions data and test results are shown in Table 3. The spiked recoveries of the two water samples were 88.90-103.2% and 90.09-107.2%, respectively, and the RSDs were less than 5.245% and 5.448%, respectively. The spiked recoveries of the three teas were 89.68-106.2%, 83.86-111.8%, and 86.17-102.6%, respectively, and the RSD values ​​were less than 7.336%, 6.024%, and 6.348%, respectively. The results show that the method has a high recovery rate.

[0122] Table 3

[0123]

[0124]

[0125] ND ※ : Not detected or below the detection limit.

[0126] In summary, the sea urchin-shaped hollow metal-organic framework material (H-ZIF-8@Zn-MOF-74) prepared in the present invention has a uniform core-shell structure, a large specific surface area, a highly ordered mesoporous structure and a high selective adsorption capacity, and has a high extraction efficiency and equilibrium adsorption capacity for common ONPs, so it can be used to effectively extract ONPs in complex matrices.

[0127] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A metal organic framework material with a hollow structure, characterized in that: The metal organic framework material with a hollow structure is named H-ZIF-8@Zn-MOF-74, and the metal organic framework material is pre-synthesized from ZIF-8 with 2-methylimidazole and Zn(NO3)2·6H2O, and then ligands are converted and etched with 2,5-dihydroxyterephthalic acid; A single metal organic framework material is a shell structure, and the shell structure includes a hollow shell layer and a plurality of rod-shaped structures located outside the hollow shell layer.

2. The metal organic framework material with a hollow structure according to claim 1, characterized in that: The shell structure is in the shape of a sea urchin; And / or, the diameter of a single metal organic framework material is 150-250 nm.

3. The method for preparing a metal organic framework material having a hollow structure according to claim 1 or 2, comprising the following steps: 1) Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in an alcohol solvent and react at 50-80°C for 10-30 minutes; dry the obtained product at 50-70°C to obtain ZIF-8; 2) dissolving 2,5-dihydroxyterephthalic acid and ZIF-8 in DMF solvent respectively, and mixing to obtain a mixture; The mixture was sealed in a reactor and reacted at 100-120° C. for 9-15 hours. The product obtained by post-treatment was dried at 50-70° C. to obtain H-ZIF-8@Zn-MOF-74.

4. The method for preparing a metal organic framework material having a hollow structure according to claim 3, characterized in that: It also includes at least one of the following technical features: 1a) In step 1), 2-methylimidazole is first dissolved in an alcohol solvent to obtain a solution A; Zn(NO3)2·6H2O is dissolved in an alcohol solvent to obtain a solution B; and solution A is added to solution B to react; 1b) In step 1), the post-treatment is to wash the product with an alcohol solvent and ultrapure water for 1 to 5 times respectively; 1c) In step 1), the alcohol solvent is selected from C1 to C4 alcohols; 1d) In step 1), the mass ratio of 2-methylimidazole to Zn(NO3)2·6H2O is 2 to 2.5:1; 1e) In step 1), the mass of the alcohol solvent is 5 to 10 times the mass of 2-methylimidazole, and the mass of the alcohol solvent is 15 to 20 times the mass of Zn(NO3)2·6H2O; 2a) In step 2), the mass ratio of 2,5-dihydroxyterephthalic acid to ZIF-8 is 1:2.5-2.8; 2b) In step 2), the mixture is reacted in a stainless steel autoclave; 2c) In step 2), the post-treatment is to wash the product with DMF and methanol solvents for 1 to 5 times respectively.

5. A solid phase microextraction agent, comprising a solid phase carrier and a coating coated on the solid phase carrier, characterized in that: The coating is the metal organic framework material as claimed in claim 1 or 2; The solid phase carrier is stainless steel wire.

6. The solid phase microextraction agent according to claim 5, characterized in that The coating and the solid support are connected by physical adhesion; and / or, the coating has a thickness of 5 to 30 nm; And / or, the stainless steel wire is aqua regia modified stainless steel wire.

7. The method for preparing the solid phase microextraction agent according to claim 5 or 6, characterized in that: The steps include: 1) immersing the stainless steel wire in an adhesive that is completely dispersed by ultrasonic wave, and using the adhesive to attach the metal organic framework material to the stainless steel wire to obtain a uniform coating; repeating the operation to obtain a solid phase microextraction agent with a target coating thickness; 2) Drying the coated solid phase microextraction agent at 110-130° C. for 1-5 hours to obtain a solid phase microextraction agent.

8. The method for preparing a solid phase microextraction agent according to claim 7, characterized in that: The stainless steel wire is aqua regia modified stainless steel wire, and the modification method is to first soak the stainless steel wire in aqua regia solution for 1 to 5 minutes, then wash it with methanol and water for 1 to 5 times respectively, and dry it at room temperature; and / or, the target coating thickness is 5 to 30 nm; And / or, the adhesive is a mixed solution of silicone sealant and toluene, and the concentration of silicone sealant in the adhesive is 450-550 mg / mL -1 .

9. Use of the metal organic framework material with a hollow structure as claimed in claim 1 or 2 in water treatment.

10. Use of the solid phase microextraction agent according to claim 5 or 6 in water treatment.

Citation Information

Cited By

  • Cuboid zeolite imidazate skeleton-8 nanoparticles as well as preparation method and application thereof

    CN120535766A

  • A cuboid zeolitic imidazolate framework-8 nanoparticle and a preparation method and application thereof

    CN120535766B